Risk management of broadcasting media in Indonesia - Harmonis Harmonis; Amin Shabana (ProTVF, 2022)
Risk management for an institution is a necessity. It is because risk has become an integral part of the institution. For this reason, every institution, whether political, business, or social, must be appropriately managed. In that context, the study aims to find out about the form of risk management carried out by one of the independent state institutions that are trusted to broadcast, namely the Central Indonesian Broadcasting Commission (KPI). The main theories used are Broadcasting and Risk Management. This study uses qualitative methods and is supported by field data through data collection through in-depth interviews and involved observations. The study results show that the Central KPI must manage many risks in managing media broadcasts. Among these risks are unethical advertisements and broadcast protests due to the low socialization of the Broadcasting Code of Conduct and Broadcast Program Standards and complaints from the television reading community. Therefore, the Indonesian Broadcasting Commission seeks to manage this risk through the School of Broadcasting Behavior Guidelines and Broadcast Program Standards (P3SPS) program and research on the quality of broadcast programs. With this program, stakeholders, journalists, and television broadcast media, as well as experts, are involved in schools and research. The socialization results made quality television broadcasts more enthusiastic, and finally, the Indonesian Broadcasting Commission issued the KPI award, which was given to the most ethical broadcasting institution.